Aerosol indirect effects on glaciated clouds. Part I: Model description. (26th April 2016) - Kudzotsa, Innocent; Phillips, Vaughan T. J.; Dobbie, Steven; Formenton, Marco; Sun, Jiming; Allen, Grant; Bansemer, Aaron; Spracklen, Dominick; Pringle, Kirsty
Abstract : Various improvements were made to a state‐of‐the‐art aerosol–cloud model and comparison of the model results with observations from field campaigns was performed. The strength of this aerosol–cloud model is in its ability to explicitly resolve all the known modes of heterogeneous cloud droplet activation and ice crystal nucleation. The model links cloud particle activation with the aerosol loading and chemistry of seven different aerosol species. These improvements to the model resulted in more accurate prediction especially of droplet and ice crystal number concentrations in the upper troposphere and enabled the model to directly sift the aerosol indirect effects based on the chemistry and concentration of the aerosols. In addition, continental and maritime cases were simulated for the purpose of validating the aerosol–cloud model and for investigating the critical microphysical and dynamical mechanisms of aerosol indirect effects from anthropogenic solute and solid aerosols, focusing mainly on glaciated clouds. The simulations showed that increased solute aerosols reduced cloud particle sizes by about 5 μ m and inhibited warm rain processes. Cloud fractions and their optical thicknesses were increased quite substantially in both cases. Although liquid mixing ratios were boosted, there was however a substantial reduction of ice mixing ratios in the upper troposphere owing to the increase in snow production aloft. These results are detailed in the subsequent parts of this study.